Performance assessment of a RIS-empowered post-5G/6G network operating at the mmWave/THz bands - Velez, V. (2023)
Reconfigurable Intelligent Surfaces (RISs) are considered to be a key enabling technology for 6G as they can potentially provide a boost in performance with a high energy efficiency. RISs rely on the use of arrays with a large number of low-cost quasi-passive reflecting elements which can be individually tuned in order to shape the radio wave propagation. This can effectively enable the implementation of smart radio environments, increasing the capacity and improving the coverage of the system. Since most RISs related studies focus on evaluating the gains of RIS based solutions in simplified communication scenarios, in this paper we investigate the potential benefits of RISs when integrated into future wireless networks within the context of post-5G/ 6G systems. With this aim, we present an iterative algorithm for accomplishing the joint design of the access point precoder and phase-shifts of the RIS elements considering a multi-stream multiple-input multiple output (MIMO) orthogonal frequency division multiplexing (OFDM) link. Based on this approach, we then present the system-level evaluation of a RIS-aided post-5G/6G network deployment operating in two different bands, mmWave and sub-THz, and which considers both near-field and far-field propagation models. The results obtained in two different environments namely, Indoor Open Office (IOO) and Urban Micro Truncated (UMT), show that the adoption of the proposed RIS-based approach can effectively improve the throughput and coverage area.